Level Stress, Anxiety, Depression, and Well-being among Parents of Children with ADHD in Indonesia - Dianasari; Dianasari (International Conference on Sustainable Health Promotion, 2023)
Caring for children with ADHD is an essential responsibility for parents, as they need to ensure proper treatment and support their mental health. To gain insight into the well-being of these parents, we conducted an online survey through the WhatsApp group ’Smart Parent Anak ADHD’. The group consists of 300 members from Indonesia, and 65 of them, which is 22% of the group, responded to the survey. We used the DASS tool to measure levels of stress, anxiety, and depression, as well as the WHO well-being instrument to assess caregiver well-being. The results revealed that 60% of parents experienced symptoms of anxiety, ranging from mild to very severe, while 62% experienced mild to very severe depression. Moreover, out of all the respondents, only 20, which is 30.8%, received a well-being score of 60 or higher (out of 100).